2020
DOI: 10.1016/j.msard.2020.102472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the rate of COVID-19 infection, hospitalization and death among Iranian patients with multiple sclerosis

Abstract: Background: COVID-19 is increasingly expanding all over the world. People who have an underlying disease or taking immunosuppressive drugs are generally more likely to be infected than the others. Multiple sclerosis (MS) patients may also be at risk of the disease and its complications depending on the medication they are taking. In this study, we evaluated a large population of patients with MS with different disease modifying drugs to show if any of them increases the risk. In addition, this study evaluates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
102
5
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 32 publications
(41 reference statements)
7
102
5
2
Order By: Relevance
“…Overall, the data of 2493 MS patients and 37 NMOSD patients were reported with COVID-19. ( Table 1 , 2 ) ( Sahraian et al, 2020 , Safavi et al, 2020 , Bowen et al, 2020 , Louapre et al, 2020 , Dalla Costa et al, 2020 , Parrotta et al, 2020 , Barzegar et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 , Sahraian et al, 2020 , Nesbitt et al, 2020 , Chaudhry et al, 2020 , Castillo Álvarez et al, 2020 , Shalhoub, 2020 , Delbue et al, 2007 , Berger and Brandstadter, 2020 , Maillart et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 , Crescenzo et al, 2020 , Mehta et al, 2019 , Maghzi et al, 2020 , Möhn et al, 2020 , Bollo et al, 2020 , Ciardi et al, 2020 , Valencia-Sanchez and Wingerchuk, 2020 , Foerch et al, 2020 , Barzegar et al, 2020 , Chiarini et al, 2020 , Gomez-Mayordomo et al, 2020 , Mallucci et al, 2020 , Giovannoni et al, 2020 , Borriello and Ianniello, 2020 , Louapre et al, 2020 , Aguirre et al, 2020 , Rimmer et al, 2020 , Luna et al, 2019 , Carandini et al, 2020 , Matías-Guiu et al, 2020 , Guevara et al, 2020 , Fernández-Díaz et al, 2020 , Amor et al, 2020 , Fiorella and Lorna, 2020 , Dersch et al, 2020 , De Angelis et al, 2020 , Celius, 2020 , Jack et al, 2020 , Suwanwongse and Shabarek, 2020 , Ghajarzadeh et al, 2020 , Montero-Escribano et al, 2020 , Novi et al, 2020 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the data of 2493 MS patients and 37 NMOSD patients were reported with COVID-19. ( Table 1 , 2 ) ( Sahraian et al, 2020 , Safavi et al, 2020 , Bowen et al, 2020 , Louapre et al, 2020 , Dalla Costa et al, 2020 , Parrotta et al, 2020 , Barzegar et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 , Sahraian et al, 2020 , Nesbitt et al, 2020 , Chaudhry et al, 2020 , Castillo Álvarez et al, 2020 , Shalhoub, 2020 , Delbue et al, 2007 , Berger and Brandstadter, 2020 , Maillart et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 , Crescenzo et al, 2020 , Mehta et al, 2019 , Maghzi et al, 2020 , Möhn et al, 2020 , Bollo et al, 2020 , Ciardi et al, 2020 , Valencia-Sanchez and Wingerchuk, 2020 , Foerch et al, 2020 , Barzegar et al, 2020 , Chiarini et al, 2020 , Gomez-Mayordomo et al, 2020 , Mallucci et al, 2020 , Giovannoni et al, 2020 , Borriello and Ianniello, 2020 , Louapre et al, 2020 , Aguirre et al, 2020 , Rimmer et al, 2020 , Luna et al, 2019 , Carandini et al, 2020 , Matías-Guiu et al, 2020 , Guevara et al, 2020 , Fernández-Díaz et al, 2020 , Amor et al, 2020 , Fiorella and Lorna, 2020 , Dersch et al, 2020 , De Angelis et al, 2020 , Celius, 2020 , Jack et al, 2020 , Suwanwongse and Shabarek, 2020 , Ghajarzadeh et al, 2020 , Montero-Escribano et al, 2020 , Novi et al, 2020 , …”
Section: Resultsmentioning
confidence: 99%
“… Confirmed patients Death Suspicious patients TotalPatients TotalDeath (%) Interferon beta ( Safavi et al, 2020 , Bowen et al, 2020 , Louapre et al, 2020 , Parrotta et al, 2020 , Barzegar et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 , Sahraian et al, 2020 , Chaudhry et al, 2020 , Castillo Álvarez et al, 2020 , Sormani et al, 2020 , Evangelou et al, 2020 , Loonstra et al, 2020 ) 61 74 135 0 Interferons/GA ( Dalla Costa et al, 2020 , Nesbitt et al, 2020 ) - - 84 84 0 GA ( Bowen et al, 2020 , Louapre et al, 2020 , Parrotta et al, 2020 , Sahraian et al, 2020 , Maillart et al, 2020 , Chaudhry et al, 2020 , Sormani et al, 2020 , Evangelou et al, 2020 , Loonstra et al, 2020 , Kataria et al, 2020 ) 67 1-71 -year-old,Male, SPMS Comorbidities: Venus Thrombo embli and obesity ( Parrotta et al, 2020 ) 2-64 -year-old, Male, RRMS, EDSS: 2, no comorbidity. ( Sormani et al, 2020 ) 73 140 2(1.4%) DMF ( Louapre et al, 2020 , Parrotta et al, 2020 , Barzegar et al, 2020 , Ciampi et al, 2020 , Mantero et al, 2020 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis about the diseases of the respiratory system and the neoplasms as prognosis factors for the mortality through COVID-19 is not con rmed in our study. Therefore, it is likely that patients died because of the impact and virulence of the SARS-CoV-2 infection over comorbidities like hypertension, diabetes mellitus or obesity, in combination with age and gender [37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that DMTs, especially the first‐generation drugs such as IFN‐β and glatiramer acetate, are not related to severe infection in MS patients. However, very recent reports about the risk of COVID‐19 infection in MS patients demonstrated that there is no correlation between incidences of COVID‐19 in the MS patients 48–50 . However, Sahraian et al 48 showed a higher risk of hospitalization in the MS patients infected by COVID‐19 as compared with the general population.…”
Section: The Effect Of Dmts On Ms Patients With Covid‐19mentioning
confidence: 99%